O Comportamento empreendedor dos proprietários/gerentes das micro e pequenas empresas do setor de beneficiamento de frutos e laticínios na região do Baixo Jaguaribe - CE - Mesquita, Jarina Maia Alvino de (2015)
In micro and small business, it’s the owner that is the source of all guidelines for the company operation and its from his ideas that the business develops, having, the owner, a key role on the success or failure of the company. His characteristics naturally influences in the performance of the enterprise and his behavior are a preponderant factor for the company success. Thus, we show a study that have as main objective analyze the entrepreneurial behavior of the owners/leaders from the micro and small industrial business from fruit and dairy processing sector in the Baixo Jaguaribe region, CE. The study is featured as quantitative and was accomplished through a survey that sought identify socio economic, entrepreneurial and comportamental behaviours following as proposed by McClelland et al (1987) and UNCTAD (2009), studied by descriptive and factorial analysis. The results leads that these entrepreneurs have a distinct profile for being older, better educated and with lower income that the nationwide average profile. The companies are established in the market for over 10 years with a small number of employees and perform some of the basic administrative controls. The individuals studied can be considered entrepreneurs, showing a high degree of need for achievement and a low degree of need for power. The results also suggests that the entrepreneurial behaviour can have a life cycle, manifesting themselves in higher or lesser degree according the company's age and time.